The perceptions of nurses regarding the communication and cognition of persons with mild Alzheimer’s dementia, within the Tygerberg district of Cape Town - Jeske, Corinna (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSL&HT)--Stellenbosch University, 2017.